$(a) \lim\limits_{n\to \infty} \left(1+e-\displaystyle\sum_{i=0}^n \frac1{k!}\right)^{n!}$

$(b) \lim\limits_{n\to \infty} \left(1+e-\displaystyle\sum_{i=0}^n \frac1{k!}\right)^{(n+1)!}$

I know $\lim\limits_{n\to \infty} \displaystyle\sum_{i=0}^n \dfrac1{i!} = e$, but I don't know how to start the above :(

Thanks for (a). How to do (b)?



$$s_n = \sum_{i=0}^n \frac{1}{i!}$$

Since you already know $s_n \to e$, we can use

$$\lim_{x \to x_0 }(1+f(x))^{\frac{1}{f(x)}} = e,\ \text{when}\ \lim_{x\to x_0}f(x) = 0$$

to write the first limit (a) as:

$$\lim_{n\to \infty}(1+e-s_n)^{n!} = \lim_{n\to \infty}\left[(1+e-s_n)^{\frac{1}{e-s_n}}\right]^{n! (e-s_n)} = e^{L}$$


$$L = \lim_{n\to \infty} n!(e-s_n)$$

We can evaluate $L$ using Cesaro-Stolz:

$$L = \lim_{n\to \infty} \frac{e-s_n}{\frac{!}{n!}} = \frac{s_n-s_{n+1}}{\frac{1}{(n+1)!}-\frac{1}{n!}} = \lim_{n\to \infty}\frac{-\frac{1}{(n+1)!}}{-\frac{n}{(n+1)!}}=\lim_{n\to \infty}\frac{1}{n} = 0$$

So the first limit equals $e^0 = 1$. We can solve (b) very similarly, I leave it to you (the result is $e$).

  • $\begingroup$ you wrote $\lim_{f(x) \to 0}(1+f(x))^{\frac{1}{f(x)}} = e$, but I think you meant "x" instead of $f(x)$ right? $\endgroup$ Feb 2 '20 at 19:43
  • 1
    $\begingroup$ @OlivierRoche, I meant this limit is true for any $f(x)$ whose limit is $0$. Maybe the formulation is not clear enough. I edited. $\endgroup$
    – LHF
    Feb 2 '20 at 19:45
  • $\begingroup$ All clear, thanks. But then I get $L = \lim \frac{n!}{e-s_n}$. What did I miss? $\endgroup$ Feb 2 '20 at 20:07
  • $\begingroup$ @OlivierRoche, In the exponent you write $n! = \frac{1}{e-s_n} \cdot n!\cdot (e-s_n)$. But $\frac{1}{e-s_n}$ vanishes with the limit I wrote (to get that $e$) and in the exponent remains $n!\cdot (e-s_n)$ $\endgroup$
    – LHF
    Feb 2 '20 at 20:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.